Mekanizmaların tasarımında uzman sistemler - (:unkn) unknown (My University, 2000)
Bilgisayar Bilimlerinin bir branşı olan Yapay Zeka (YZ) teknikleri hemen hemen bütün mühendislik disiplinlerine girmeye başlamıştır. Uzman Sistemler bir YZ tekniği olup ilk YZ araştırmacılarının ana hedeflerinden olan farklı problemleri çözebilen genel amaçlı zeki yazılım ortamları oluşturma konusunda hızlı gelişmeler göstermektedirler. Uzman Sistemlerin uygulama alanı bulduğu alanlardan birisi mekanizmalardır. Bu çalışmada, mekanizma tasarımı çalışmalarının ışığında bilgi mühendisliği teknolojisinin altyapısı gözden geçirilmiştir. Programlama ortamında mekanizmaların tanımlanmaları ve Uzman Sistem teknolojisinin mekanizma tasarımı uygulamaları tanıtılmıştır. Mekanizma tasarımında bazı Uzman Sistem uygulamaları incelenmis ve kapasiteleri tartışılmıştır.

The techniques of Artificial Intelligence (AI), a branch of Computer Science, have been rapidly entering into almost all disciplines of engineering. Expert Systems are the most encouraging product of Al and present a departure from the original aim of pineering AI researchers to built general purpose intelligent tools for solving variety of problems., one of which is the design of mechanical systems and mechanisms. In this work, the technology underlying the field of knowledge engineering is reviewed with the examples of mechanism design to highlight the nature of expert systems and their infrastructure. The application of Expert Systems technology in the design of mechanisms is discussed together with the representation techniques of mechanisms for programming purpose. Some of the recent applications of expert systems in mechanism design are described and their capabilities are discussed.
Expert systems in mechanism design